Anthropometric profile of elite acrobatic gymnasts and prediction of role performance - Taboada-Iglesias,Y.; Gutiérrez-Sánchez, Á.; Vernetta Santana, M. (The Journal of Sports Medicine and Physical Fitness, 2016)
BACKGROUND: This study is aimed at determining the anthropometric profile of acrobatic gymnasts, differentiating on the basis of their role.